Formulation and evaluation of ointment containing hydroalcoholic extract derived from the bark of Moringa oleifera for wound healing activity in rat model - Sahu, Himanshu; Satapathy, Trilochan; Chandrakar, Shashikant; Gupta, Puahpa Prasad; Sahu, Poonam; Sahu, Akhilesh (Journal of Applied Pharmaceutical Research, 2024)
Background: This study aimed to assess the effectiveness of a hydroalcoholic extract derived from the bark of Moringa oleifera in facilitating the healing process of second-degree burns wounds. Moreover, a comprehensive assessment was carried out on standardized M. oleifera bark to ascertain its physiochemical characteristics, botanical compound layout, and antioxidant activity, all of which play a crucial role in its capacity to facilitate the healing process of burns. Methods: For 14 days, the efficacy of ointments containing a hydroalcoholic extract of M. oleifera bark at concentrations of 5% and 10% was evaluated for treating second-degree burns in rats. Additionally, histological analysis was conducted on skin tissue samples. Results: The M. oleifera bark extract exhibited TPC (52.56 mg/gm of dried extract) and TFC (84.33 mg/gm of dried extract) value along with antioxidant activity (IC50 value of 0.98 µg/ml) for radical scavenging, in the presence of several phytochemicals. The most favorable outcomes were achieved using a 10% ointment composition, demonstrating a wound closure and tissue repair rate of 83.04 ± 0.89%, along with a noteworthy decrease in tissue oxidative stress indicators. Histological investigations have verified the wound-healing properties of M. oleifera bark extract. Conclusion: Due to its significant antioxidant properties and its capacity to create a moist environment for wounds, M. oleifera has the potential to serve as a natural treatment for burns. Additional clinical trials are recommended to validate the efficacy of M. oleifera bark extract as a therapeutic agent for wound healing.